Rede social e papéis de gênero de casais ribeirinhos de uma comunidade amazônica - SILVA, Simone Souza da Costa (2013)
This study describes the social network of two couples from a bordering community (Araraiana River, Municipality Ponta de Pedras, Marajó Island/Pará). Data were collected through a socio demographic inventory, a routine inventory and a field diary and analyzed by a network map. It was observed that the relation of the couples is based on economic and work alliances, company for leisure or religious activity. It has also been found that these relationships are marked by gender patterns which delimit the environments of daily activities, define the status that each one holds in the family and condition the formation of bonds in social networks.